MENGAPA TERJADI GROWTH WITHOUT DEVELOPMENT DI PROVINSI KALIMANTAN TIMUR? - Kuncoro, Mudrajad; Idris, Ahmad Nafis (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
This study attempts to examine to what extent growth without development has occured in East Kalimantan (Kaltim)? It will use several analyses, in particular regional typology based on economic growth and Gross Regional Domestic Product (GRDP), leading sectors and subsectors, location pattern of those leading sectors and subsectors, and the structural transformation. To analyse the effects of regional autonomy on Kaltim, the data used in this research are divided into two periods: before (1993-2000) and after regional autonomy (2001-2007). By using quantitative-descriptive analyses, our findings find that: first, miningexcavation has persisted to be the major leading sector in Kaltim. Second, leading subsectors in Kaltim comprise forestry, oil and gas, nonoil and gas industry, and wholesale-retail commerce. Third, the leading subsectors tend to despecialize in Kaltim during the implementation of regional autonomy. Fourth, structural transformation does not occur in all kabupaten/kota of Kaltim confirming that Kaltim is a good provincial example for growth without development.